DAMPAK PSIKOLOGI DATING VIOLENCE REMAJA DI SMA TUGAMA MEDAN - Hasmayni, Babby (JURNAL DIVERSITA, 2015)
This Research aim to know the relation of dating violence with the psychological impact feltadolescent. Dating Violence is all kind of action having enforcing element, pressure, mutilation,and worthless of physical and also psychological that happened in relation dating. Affect thephysical can in the form of contusion broken bone, while psychical impact can in the form ofstress, depression , solitude, abundant dread (Herman, 2008). This research population is allstudent of SMA Tugama owning girlfriend amount to 32 people consisted of by 11 men and 21women. The collects of sample used by technique of snowball sampling. Snowball sampling isprimeval determination sample technique of its amount is small, big later then. In determinationsample, is first of all selected by one or two people, later then this two people is ordered tochosen its friends to be made by sample. So further, so that sum up the sample of more andmore ( Sugiono, 2004). The data of both variable are collected by rating scale. There arepsychological conditions and dating violence scale. Pursuant to result of calculation ofcorrelation of r Product Moment known by that there is relation which are positive betweendating violence to psychological condition of student in SMA Tugama with the value ofcoefficient rxy = 0,888 ; p < 0, 05. Thereby research hypothesis accepted. Besides determinantcoefficient (r2) from relation of above is equal to r2 = 0, 789. This matter indicate that thedating violence influence the psychological condition of student equal to 78,9 persent.